THE EFFECT OF CREATIVITY AND INNOVATION ON CUSTOMER SATISFACTION WITH THE SIANG HARI BANDUNG PROJECT - Adriansyah Eka Putra; Anisa Payar Angraeni; Kinanti Prianggara Putri; Yuli Surya Fauzia Pertami (TOPLAMA, 2026)
This research aims to find out the relationship between creativity and innovation to customer satisfaction Siang Hari Project Bandung. This research uses quantitative research methods with an associative research approach. Sampling techniques using probability sampling techniques, namely simple random sampling with a sample of 90 people. Data analysis techniques using Statistical Pacakge for Social Science (SPSS)method. Based on the results of the study, found that: (1) Creativity positively affects consumer satisfaction with a regression value of 0.035 and a significance level of 0.082. (2) Innovation positively affects consumer satisfaction with a regression value of 0.003 and a significance level of 0.082 (3) creativity and innovation simultaneously positively affects customer satisfaction with a significance level of 0.000, smaller than < 0.05 and F value calculates 36.345 F value count > F table. Then from the data obtained, it was found that creativity was 82%, innovation and customer satisfaction were 81%, that is, the continuum line was in the good category. The magnitude of the contribution of the influence of creativity and innovation on consumer satisfaction is 45.5% and the remaining 54.5% is explained by other factors not examined. Then Ha is accepted, which means that creativity and innovation have a significant effect on customer satisfaction at the Bandung Afternoon Project. So it can be concluded the creativity and innovation have a significant and positive effect both partially and simultaneously on consumer satisfaction. The application of creativity and innovation based on the results of research has been implemented well, therefore it is expected that the Afternoon Project company remains aligned in implementing this creativity and innovation, and can even be continuously improved.